RETRACTED: Analysis of the influence of enterprise managers’ overconfidence on the overinvestment behavior of listed companies under the media reports - SO, Michael (Frontiers in Psychology, 2022)
At present, there is a common overinvestment behavior among listed companies in various countries, which seriously reduces the overall resource allocation efficiency of the market. With the rise of behavioral finance, it has become a new direction to study the influence of managers' "irrational characteristics" on enterprise overinvestment. With the rapid rise of the media industry, media reporting, as an external governance mechanism, supplements the capital market supervision system and has a huge impact on the investment behavior of enterprises. How media reports affects overinvestment and whether it can curb overinvestment caused by managers' overconfidence is still worthy of further study. This paper took 6012 A-share listed companies from 2013 to 2021 as samples, and based on the perspective of "media reports", studies the impact of managers' overconfidence on overinvestment; explores whether positive and negative media reports have a moderating effect between overconfidence and overinvestment; studies the moderating effect of media reports under different marketization processes. Empirical conclusions: (1) Managers' overconfidence will lead to overinvestment of enterprises. (2) Positive media reports will aggravate the overinvestment caused by managers' overconfidence; negative reports can inhibit the overinvestment caused by managers' overconfidence. (3) In regions with higher marketization, positive media reports play a more significant role in aggravating overconfidence and leading to overinvestment; in regions with lower marketization, negative reports play a stronger role in restraining overconfidence and overinvestment.